Efficacy evaluation of pepsin enzyme-based gel in chemo-mechanical caries removal on primary anterior teeth: a randomized controlled clinical study - Abo Alhuda, Douaa; Rajab, Anas; Shaadouh, Rashad; Katbeh , Imad; Tuturov , Nikolay; Abo Arrag, Ettihad (Brazilian Dental Science, 2022)
Objective: To evaluate the efficacy of a new pepsin enzyme-based gel compared with Carisolv as a CMCRagent. Clinical and radiographical evaluations of recurrent caries were made 3 and 6 months after treatment.Material and Methods: A split-mouth designed randomized controlled clinical study was carried out on 40 primaryanterior teeth of children aged between 4-7 years. Pepsin enzyme-based gel and Carisolv solution were appliedto carious lesions until complete removal of caries. The efficacy of both agents was evaluated by the number ofapplication times to remove all caries. Recurrent caries were evaluated clinically and radiographically after 3 and 6months of treatment. Results: Results showed no statistically significant differences in the efficacy of caries removalby the number of application times (P = 0.919). Concerning recurrent caries, clinical and radiographical evaluationafter three and six months showed no statistically significant differences between the two groups (P = 0.574, P =0.547, respectively). Conclusion: Pepsin enzyme-based gel can be considered similar to Carisolv gel regarding itsefficacy as a CMCR agent for small carious lesions on primary anterior teeth in children aged 4-7 years old.KEYWORDSCarisolv; Chemo-mechanical caries removal; Pepsin enzyme; Caries; Minimally invasive dentistry.